I want to make the following recursive function: xm+1 = xm - F(x)/F'(x)

so I did this:

"X="?->X

"F(X)="?->A

"F'(X)="->B

Lbl 1: X-(A)/(B ) -> X (display)

Goto 1

so at starting the program

for a function like xm+1 = xm - (xm^3 -100)/(3*xm^2)

I introduce

4

X^3-100

3*X^2

But when the program makes the second iteration it doesn't changes the X paramater from functions A and B

so, at the first iteration gives

4.75, but at the second gives 5.5 instead of 4.644044!

How can I do what I want then?

Thanks

**Edited by troublex, 26 March 2011 - 12:54 PM.**